Determinants of outcome among patients with acute liver failure listed for liver transplantation in the United States. Issue 4 (April 2016) - Reddy, K. Rajender; Ellerbe, Caitlyn; Schilsky, Michael; Stravitz, R. Todd; Fontana, Robert J.; Durkalski, Valerie; Lee, William M.; ,
Abstract : Analyses of outcomes after acute liver failure (ALF) have typically included all ALF patients regardless of whether they were listed for liver transplantation (LT). We hypothesized that limiting analysis to listed patients might provide novel insights into factors associated with outcome, focusing attention on disease evolution after listing. Listed adult ALF patients enrolled in the US Acute Liver Failure Study Group registry between 2000 and 2013 were analyzed to determine baseline factors associated with 21‐day outcomes after listing. We classified 617 patients (36% of overall ALF group) by 3‐week outcome after study admission: 117 were spontaneous survivors (SSs; survival without LT), 108 died without LT, and 392 underwent LT. Only 22% of N ‐acetyl‐ p ‐aminophenol (APAP) ALF patients were listed; however, this group of 173 patients demonstrated greater illness severity: higher coma grades and more patients requiring ventilator, vasopressor, or renal replacement therapy support. Only 62/173 (36%) of APAP patients received a graft versus 66% for drug‐induced liver injury patients, 86% for autoimmune‐related ALF, and 71% for hepatitis B–related ALF. APAP patients were more likely to die than non‐APAP patients (24% versus 17%), and the median time to death was sooner (2 versus 4.5 days). Despite greater severity of illness, the listed APAP group still had a SS rate of 40% versus 11% for non‐APAP causes ( P < 0.001). APAP outcomes evolve rapidly, mainly to SS or death. Patients with APAP ALF listed for LT had the highest death rate of any etiology, whereas more slowly evolving etiologies yielded higher LT rates and, consequently, fewer deaths. Decisions to list and transplant must be made early in all ALF patients, particularly in those with APAP ALF.